Individual Well-Being and the Allocation of Time Before and After the Boston Marathon Terrorist Bombing - Andrew E. Clark; Elena G. F. Stancanelli (Institute for the Study of Labor (IZA), 2016)
There is a small literature on the economic costs of terrorism. We consider the effects of the Boston marathon bombing on Americans' well-being and time allocation. We exploit data from the American Time Use Survey and Well-Being Module in the days around the terrorist attack to implement a regression-discontinuity design. The bombing led to a significant and large drop of about 1.5 points in well-being, on a scale of one to six, for residents of the States close to Boston. The happiness of American women also dropped significantly, by almost a point, regardless of the State of residence. Labor supply and other time use were not significantly affected. We find no well-being effect of the Sandy Hook shootings, suggesting that terrorism is different in nature from other violent deaths.
Keywords: I31; J21; J22; F52; 330; well-being; time use; Terrorism